Pengaruh Lingkungan Wajib Pajak, Sikap Rasional Dan Pemanfaatan Teknologi Informasi Terhadap Kepatuhan Wajib Pajak - Eneng Rahmawati; Wulandari Cahyani Putri (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of the taxpayer's environment, rational attitudes, and the use of information technology on taxpayer compliance. This type of research uses associative quantitative research. The population used in this research were students at Pamulang University, Undergraduate Accounting Study Program Semesters 1-8, Regular Ck and Cs. The sampling technique uses convinience sampling which determines the most suitable criteria for determining this research. The sampling technique used the Slovin formula so that the total sample used in this research was 100 respondents. The data analysis technique uses multiple linear regression with the help of SPSS version 28 software. The results of this research show that simultaneously the taxpayer's environment, rational attitudes and the use of information technology have a significant effect on taxpayer compliance. Meanwhile partially, the taxpayer's environment has no effect on taxpayer compliance. Rational attitudes have a significant effect on taxpayer compliance. The use of information technology has a significant effect on taxpayer compliance.